PROSES KREATIF PELUKIS KALIGRAFI ISLAM: SEBUAH PENELITIAN KUALITATIF - Nofan G Lismarwan; Fuad Nashori (Proyeksi: Jurnal Psikologi, 2010)
The aim of this study is to descriptively explore the creative process experienced by Islamic calligraphy painters. The research subjects were active muslim calligraphy painters whose age were above 21 years old and have produced more than 5 Islamic calligraphy paintings. Subjects of this research were: Munichy B. Edrees, H. Ashady and Syaiful Adnan. The data was obtained from a semi-structured interview.  The use of this method of data was intended to identify the creative process among those Islamic calligraphy painters.The results of this research on the creative process in Islamic calligraphy painters were of the followings: (1) it took a good mood and tranquil mind to paint, (2) specified situations may generate inspiration, (3) a desire to paint which were derived from the surrounding reality and occurences, both social and spiritual, (4) the painters‘ feeling of horizontal and vertical satisfaction resulting from painting. (5) the need to probe for a certain theme through the collection of relevant information, (6) the creative process influenced by religious activities, (7) the painters‘ interest and concern on specific themes, (8) the creative process influenced by technical skills of calligraphy painting, (9) the painters’ compliance to  follow their hand movements as they were believed to be inspired by Allah. There were, in fact, similarities and differences found in each calligraphy painters in their creative painting process. Keywords: creative process, calligraphy painter